2018
DOI: 10.1038/s41598-018-28235-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of a human galectin-3 variant with two ordered segments in the shortened N-terminal tail

Abstract: Among members of the family of adhesion/growth-regulatory galectins, galectin-3 (Gal-3) bears a unique modular architecture. A N-terminal tail (NT) consisting of the N-terminal segment (NTS) and nine collagen-like repeats is linked to the canonical lectin domain. In contrast to bivalent proto- and tandem-repeat-type galectins, Gal-3 is monomeric in solution, capable to self-associate in the presence of bi- to multivalent ligands, and the NTS is involved in cellular compartmentalization. Since no crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 67 publications
(91 reference statements)
1
33
0
Order By: Relevance
“…Immunopositivity for Gal‐3 was detected in the NP, and also in the other compartments. Its presence within the cells and in the matrix supports the concept of site‐specific activities, for example via its anti‐apoptotic intracellular and glycan‐dependent extracellular mechanisms involving Gal‐3‐mediated counterreceptor aggregation . A respective impact on chondrocyte survival was inferred by localization studies considering hypertrophy and in a knock‐out model, as also suggested for Gal‐3 in osteoarthritis .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Immunopositivity for Gal‐3 was detected in the NP, and also in the other compartments. Its presence within the cells and in the matrix supports the concept of site‐specific activities, for example via its anti‐apoptotic intracellular and glycan‐dependent extracellular mechanisms involving Gal‐3‐mediated counterreceptor aggregation . A respective impact on chondrocyte survival was inferred by localization studies considering hypertrophy and in a knock‐out model, as also suggested for Gal‐3 in osteoarthritis .…”
Section: Discussionsupporting
confidence: 60%
“…Its presence within the cells and in the matrix supports the concept of site-specific activities, for example via its anti-apoptotic intracellular and glycan-dependent extracellular mechanisms involving Gal-3-mediated counterreceptor aggregation. 42 A respective impact on chondrocyte survival was inferred by localization studies considering hypertrophy and in a knock-out model, as also suggested for Gal-3 in osteoarthritis. 7,43,44 In rat NP cells, Gal-3 knock-down led to increased susceptibility to FasL-induced cell death, 28 and a functional cooperation between tumor necrosis factor-α and Gal-3 on IL-1β, IL-6, and CCL2 expression had been reported.…”
Section: Discussionmentioning
confidence: 67%
“…For example, the N-terminus can move between a core-associated and a more solvent-exposed structure. Since shuttling between cellular compartments, as well as export, may involve this region as indicated with Gal-3 and its structural organization at this site [78,79], and N-terminal contact has been documented for Gal-1 around L11 in Ras-dependent growth regulation [80], tipping the balance toward one conformer or another here could be physiologically relevant, even providing a possible explanation for different intracellular routing of a galectin. Of note, the detected alterations go beyond the conformational repositioning at P4, as it affects the lectin more globally.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many crystal structures of the Gal-3 CRD have been reported [ 47 , 48 , 49 , 50 ], its N-terminal tail is highly flexible and interacts transiently with the F-face of the CRD [ 51 ], a dynamic situation that precludes crystallization of the full-length lectin. Recently, an interesting crystal structure of Gal-3 was published showing that a short peptide from Gal-3 N-terminal tail can extend the CRD F-face β-sheet [ 52 ].…”
Section: Structural Comparisons Between Gal-10 and Other Prototypementioning
confidence: 99%